Kesesuaian Penerapan Manajemen Mutu Ikan Pindan Bandeng (Chanos chanos) Terhadap Standar Nasional Indonesia - Elis Masrifah; Bambang Pramudya Noorachmat; Anggraini Sukmawati (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
Fish processing is an important role in post-harvest activities, because fishery products are perishable goods. Therefore we need a fast and precise handling to maintain its quality before it reaches the consumer. There are many kind of fish processing, both traditional and modern such as salting, boiling, and smoking. Entering of the ASEAN Economic Community (AEC) in 2015, fishing industries is not less important than other sectors, quality of fishery products and competitiveness is very necessary. To improve the quality of fishery products is should be control the processing and apply of food safety management systems such as Integrated Quality Management Program based on the concept of Hazard Analysis Critical Control Point (HACCP). One of fish processing units was existing in Bogor is Cindy Group (Small Medium Enterprises), they are producing preserved fishmilk. The purposes of the study are: (1) to analyze the level of implementation of the basic eligibility (GMP and SSOP) at Cindy Group, (2) to analyze the suitability of each characteristic quality of product against the requirements of SNI 2717: 2009. The study was conducted at Cindy Group SMEs located Bogor regency. The research method is descriptive with 30 respondents by purposive sampling. The results showed that based on the assessment of the level of implementation of the basic eligibility (GMP and SSOP) using UPI Assessment questionnaire published by Directorate General of the processing and marketing of fishery products, Ministry of Maritime Affairs and Fisheries) showed that SMEs Cindy Group obtained SKP the feasibility value "B" consisting of 4 minor irregularities, 2 major irregularities, and 1 serious irregularities. In quality, preserved milkfish products based on the results of testing Organoleptic and chemical have good quality according to SNI  2717: 2009. The results of organoleptic test using hedonic test showed an average value over than 7 (7 is minimum figure in SNI), indicates that the product can be accepted by consumers. Overall, the level of implementation of the basic eligibility processing program on processing of preserved milkfish in Cindy Group has been quite good, percentage rate of application of the basic feasibility is 92%. This product can be registered to BSN to get the registration number of SNI and feasible to labeled SNI on product packaging.